Perlindungan Hukum terhadap Pemegang Polis Asuransi Pengangkutan - Shobirin, Muhammad Shobirin; Mujib, Abdul (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Insurance plays an important role, because it will provide protection against losses that will occur, insurance provides a huge boost to other economic developments. Unfortunately, in practice, legal protection for insurance policy holders is less protected. The problem that policyholders always experience is the difficulty of obtaining compensation payments when an event occurs. The reason why policies are not paid by insurance companies is because of the lack of knowledge of the public itself, as well as because insurance agents do not provide clear information. Factors causing non-payment of insurance claims are the failure to implement insurance principles by insurance companies or the public. This research uses a descriptive qualitative method using a basic approach and legal norms in laws and regulations and uses a descriptive method to try to explain solutions to existing problems based on data. The form of protection guaranteed in Law no. 22 of 2009 regarding passengers, namely in articles 186 and article 191 which mention protection, protection in the form of people/or goods. And if an accident occurs and results in injury or death, the legal consequences for public transportation companies are regulated by Law no. 22 of 2009 concerning road traffic and transportation in article 192 which states that public transportation companies are responsible for losses suffered by passengers who die or are injured as a result of transportation operations, unless caused by an incident that cannot be prevented or avoided or because of the Passenger's fault.